Charge collection enhancement by incorporation of gold–silica core–shell nanoparticles into P3HT:PCBM/ZnO nanorod array hybrid solar cells1. Issue 30 (14th August 2015) - Wang, Ting-Chung; Su, Yen-Hsun; Hung, Yun-Kai; Yeh, Chen-Sheng; Huang, Li-Wen; Gomulya, Widianta; Lai, Lai-Hung; Loi, Maria A.; Yang, Jih-Sheng; Wu, Jih-Jen
<x xml:space="preserve">Abstract</x> The charge collection and the efficiency of P3HT:PCBM/ZnO nanorod array hybrid solar cells are improved by the incorporation of gold–silica core–shell nanoparticles.